Impact of cash flow on earnings management in Jordan - Khaled Eriej Aburisheh; Ahmad Abdelrahim Dahiyat; Walid Omar Owais (Cogent Business & Management, 2022)
This article aimed to examine what do operate cash flow and free cash flow are to reveal the effect on earnings management? Evidence: industrial companies listed on the Amman stock exchange during the period from 2011 to 2020. Several control variables were used to examine the relationships. The survey method adopted was employed in the choosing of a sample of 56 industrial firms. The information has been extracted from the available financial reports through the use of panel data regression. The findings from the study showed that, as independent factors, free cash flow, operating cash flow, and control variables including managerial ownership and financial leverage have an impact on earnings management. However, firm size as the control variable has no impact on earnings management.
Keywords: 650; earnings management; financial leverage; firm size; free cash flow; managerial ownership; operating cash flow